Usage of PCI and long-term cardiovascular risk in post-myocardial infarction patients: a nationwide registry cohort study from Finland - Kytö V.; Prami T.; Khanfir H.; Hasvold P.; Reissell E.; Airaksinen J. (BMC (BioMed Central Ltd.), 2022)
Background: Despite currently available treatments, the burden of myocardial infarction (MI) morbidity and mortality remains prominent. The aim of this was to investigate the risk of developing subsequent cardiovascular events in MI patients.
Methods: This was an observational, retrospective cohort database linkage study using patient level data from Finland. Cox proportional hazards models were used to assess the association of risk between the preselected covariates and incidence of specific outcomes. The primary endpoints were new MI, stroke, cardiovascular mortality and overall mortality.
Results: Finnish adult MI patients alive 7 days after discharge in 2009-2012 were included. The study cohort consisted of 32,909 MI patients, of whom 25,875 (79%) survived 12 months without subsequent MI or stroke. ST-elevation MI (STEMI) was associated with lower risk of subsequent MI and overall mortality compared to non-STEMI patients. Percutaneous coronary intervention (PCI) was used two times more often in STEMI patients, but patients with prior stroke were more than two times less likely to have PCI. Dementia/Alzheimer's disease decreased the use of PCI as much as age over 85 years. Female sex was an independent factor for not undergoing PCI (OR 0.75, P<0.001 compared to men) but was nevertheless associated with lower risk of new MI and mortality (HR 0.8-0.9, P<0.001 for all). Increased age was associated with increased event risk and PCI with decreased event risk.
Conclusions: Risk of cardiovascular events and mortality after MI increases steeply with age. Although at higher risk, aging patients and those with cardiovascular comorbidities are less likely to receive PCI after MI. Female sex is associated with better survival after MI regardless of less intensive treatment in women.